Analysis of the Returns and Volatility of the Environmental Stock Leaders - Viorica Chirila (CES Working Papers, 2013)
The last years have been faced with a blasting development of the Socially Responsible Investments (SRI) worldwide even though the economic environment has been shaken by a global economic and financial crisis. The aim of this paper is to analyze the return and risk characteristics of the sustainably managed companies that pay particular attention to the environment responsibility in comparison with those that pay more attention to the corporate governance and respectively to the social responsibility. These characteristics are useful both to the individual and institutional investors as well as to the portfolio managers. For the comparative analysis we started from the study of descriptive characteristics of return and risk of indices portfolios of the environmental social and governance stock leaders and we focused on their univariate econometric modelling by means of the heteroskedastic models. The studies undertaken until now are centered on the performance obtained by the portfolios of sustainable indices and on the modelling of the volatility of sustainable indices. We would like to investigate the characteristics of return and risk of the assets of the sustainably managed companies that could attract active investors towards the sustainably managed companies that pay particular attention to the environment responsibility in comparison with those paying increased attention to the corporate governance and respectively to the social responsibility.
Keywords: G15; C58; 330; financial market; risk; return; heteroskedastic models Romania